A Technique of Forced Expiratory Noise Time Evaluation Provides Distinguishing Human Pulmonary Ventilation Dynamics During Long-Term Head-Down and Head-Up Tilt Bed Rest Tests Simulating Micro and Lunar Gravity - Malaeva, Veronika V.; Korenbaum, Vladimir I.; Pochekutova, Irina A.; Kostiv, Anatoly E.; Shin, Svetlana N.; Katuntsev, Vladimir P.; Baranov, Viktor M. (Frontiers in Physiology, 2018)
An estimating the effect of microgravity/hypogravity on pulmonary ventilation function remains topical. Recently developed acoustic technique based on evaluation of the forced expiratory noise time (FETa) was hypothesized to be a promising tool for this aim. The objective of the study is an estimation of FETa ability to assess dynamics of human pulmonary ventilation function in bed rest tests simulating micro and lunar gravity. The FETa in frequency band of 200-2000 Hz recorded above human trachea was evaluated. Basic spirometric indices of pulmonary ventilation function were used as a reference. The 21-day exposure to 6 degree head-down tilt (HDT) bed rest, simulating microgravity, and 9.6 degree head-up tilt bed rest with head-zero tilt rest intervals (HUT+HZT), simulating lunar gravity, in statistically identical subgroups of 5 and 6 healthy male volunteers were studied. In the course of HDT bed rest a significant elongation of FETa was found in relation to background measurements in “sitting” position. The effect corresponded to significant decrease of basic spirometric indices. Moreover FETa provided reliable discrimination of HDT and HUT+HZT tests, while spirometric indices did not. Additionally FETa provided revealing significant negative long-term dynamics of pulmonary ventilation function during HDT bed rest in contrast with HUT+HZT bed rest. A FETa elongation in response to HDT bed rest was attributed to an increase of aerodynamic resistance of respiratory tract. The technique seems promising to monitor human pulmonary ventilation dynamics in long-term space missions, however new studies are welcome to verify it in real spaceflight.